Degradação do corante têxtil vermelho GRLX- 220 com ozônio gerado eletroquimicamente - Santos, Patricia Kelly dos (2010)
Aqueous solutions containing the commercial azo dye Red GRLX-220 were ozonated in acid (pH 4) and alkaline (pH 12) conditions. Ozone was electrochemically generated using a laboratory-made electrochemical reactor and applied using semi-batch conditions and a column bubble reactor. The applied current density was 20.0 and 25.0 A in acidic and basic media, respectively, resulting in a current efficiency of 8.9% and 6.4%, corresponding to an ozone application rate of 0, 550 g h and 0.480, respectively. Under these conditions and after 65 minutes of ozonation resulted in a large discoloration of the effluent (99% in acidic and 97% in alkaline media). The kinetics of color removal presented a dependence on the ozonation time through the presence of two linear segments, which were interpreted using a kinetic model of pseudofirst- order. Accordingly, it proposes the formation of intermediate species that precede the final stage of degradation. Both the removal of chemical oxygen demand (COD) and totality organic carbon (TOC) were slightly higher in alkaline media which were attributed to the presence of hydroxyl radical in the oxidation step. Evaluation of the oxidation feasibility by means of the COD/TOC radio indicates that the ozonation processes in both acid and alkaline conditions leads to a reduction in recalcitrance of the soluble organic matter. The calculations performed for the residual ozone showed that the use of the gas is maximum for short reaction time. The toxicity studies showed that the ozonation byproducts present lower toxicity than the initial solution of the dye.